2012
DOI: 10.1111/j.1469-1795.2012.00600.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the genetic impact of massive restocking on wild mallard

Abstract: Captive‐bred mallards Anas platyrhynchos have been released for hunting purposes at a very large scale in Europe since the mid‐1970s. In spite of a potential genetic impact, the actual contribution of restocked mallards to the genome of the target population has received little attention. The genetic structure of modern wild mallards in the Camargue, Southern France, was assessed from two samples: one originating from shot birds in hunting bags and one from presumed wild ducks captured alive in a hunting‐free … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 52 publications
2
36
1
1
Order By: Relevance
“…Indeed, most SNPs used in this study have rather intermediate allele frequencies (Kraus et al 2011a), and comparisons with other marker sets are not straightforward. This could explain the inconsistent results regarding heterozygosity between the current study and those by Champagnon et al (2013a) and Čížková et al (2012), who found a greater difference between farmed and wild mallards based on microsatellite analyses. Even though it is commonly acknowledged that the intrapopulation genetic structure of migratory birds is largely protected by philopatric habits (Liu et al 2012) or other migratory traditions (Jonker et al 2013), there are also examples of species with no signs of genetic structure on the continental scale (Reudink et al 2011).…”
Section: Heterozygosity and Inbreedingcontrasting
confidence: 96%
See 3 more Smart Citations
“…Indeed, most SNPs used in this study have rather intermediate allele frequencies (Kraus et al 2011a), and comparisons with other marker sets are not straightforward. This could explain the inconsistent results regarding heterozygosity between the current study and those by Champagnon et al (2013a) and Čížková et al (2012), who found a greater difference between farmed and wild mallards based on microsatellite analyses. Even though it is commonly acknowledged that the intrapopulation genetic structure of migratory birds is largely protected by philopatric habits (Liu et al 2012) or other migratory traditions (Jonker et al 2013), there are also examples of species with no signs of genetic structure on the continental scale (Reudink et al 2011).…”
Section: Heterozygosity and Inbreedingcontrasting
confidence: 96%
“…Due to founder effects, inbreeding, and genetic drift, a differentiation between wild and farmed mallards could be expected. However, studies thus far on genetic differentiation give ambiguous results; Baratti et al (2009) did not find any differences using microsatellite markers, while Champagnon et al (2013a), Čížková et al (2012), and Baratti et al (2014) detected genetic differences between regional wild and farmed populations in France, Czech Republic, and Italy, respectively. Thus, more studies of genetic structure across multiple flyways are needed to assess the degree of differentiation and potential genetic homogenization at a larger spatial scale, using a common and more powerful methodological framework.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…In addition, huge numbers of farm-reared Mallards are interbreeding with their wild conspecifics. The low genetic diversity of the captive birds threatens the genetic integrity of the wild populations in Sweden, France and the Czech Republic (Cizkova et al, 2012, Champagnon et al, 2013. A well-known case of waterfowl hybridization involves the Ruddy Duck (Oxyura jamaicensis) which was introduced to the UK in the 1950s and spread to Spain where it hybridized with the endangered White-headed Duck (Oxyura leucocephala).…”
Section: Anthropogenic Introgressionmentioning
confidence: 99%